Ranganathan: An Outstanding Philosopher of Science - Bhattacharyva, G. (Journal of Information and Knowledge, 1992)
Presents an approach to scientific method and the criteria for deeming a subject-field as a science. After analysing contributions to this modelling, this paper identifies Ranganathan's spiral of Scientific Method as a basic model to the field which is an elegant approach as that of Thomas Kuhn. Feels that this contribution of Ranganathan is a seminal one.